Essays on political economy - Darbaz, Safter Burak (The University of Edinburgh, 2015)
This thesis consists of three stand-alone chapters studying theoretical models concerning a range of issues that take place within the context of political delegation: tax enforcement, political selection, electoral campaigning. First chapter studies the problem of a small electorate of workers who cannot influence tax rates but can influence their local politicians to interfere with tax enforcement. It develops a two-candidate Downsian voting model where voters are productivity-heterogenous workers who supply labour to a local firm that can engage in costly tax evasion while facing an exogenously given payroll tax collected at the firm level. Two purely office motivated local politicians compete in a winner-takes-all election by offering fine reductions to take place if the firm gets caught evading. Two results stand out. First, equilibrium tax evasion is (weakly) increasing in the productivity of the median voter as a result of the latter demanding a weaker enforcement regime through more aggressive fine reductions. Second, if politicians were able to propose and commit on tax rates as well, then the enforcement process would be interference-free and the tax level would coincide with the median voter's optimal level. These two results underline the fact that from voters' perspective, influencing enforcement policy is an imperfect substitute for influencing tax policy in achieving an optimal redistribution scheme due to tax evasion being costly. In other words, a lax enforcement pattern in a given polity can be indicative of a political demand arising as an attempt to attain a redistributive second-best when influencing tax policy is not a possibility. Second chapter turns attention to the role and incentives of media in the context of ex ante political selection, i.e. at the electoral participation level. It constructs a signalling model with pure adverse selection where a candidate whose quality is private information decides on whether to challenge an incumbent whose quality is common knowledge given an electorate composed of voters who are solely interested in electing the best politician. Electoral participation is costly and before the election, a benevolent media outlet which is assumed to be acting in the best interest of voters decides on whether to undertake a costly investigation that may or may not reveal challenger's quality and transmit this information to voters. The focus of the chapter is on studying the selection and incentive effects of changes in media's information technology. The setting creates a strategic interaction between challenger entry and media activity, which gives rise to two main results. First, an improvement in media's information technology, whether due to cost reductions or gains in investigative strength always (weakly) improves ex ante selection by increasing minimum challenger quality in equilibrium. Second, while lower information costs always (weakly) make the media more active, an higher media strength may reduce its journalistic activity, especially if it is already strong. The intuition behind this asymmetry is simple. While both types of improvements increase media's expected net benefits from journalism, a boost to its investigative strength also makes the media more threatening for inferior challengers at a given level of journalistic activity. Combining this with the first result implies that the media can afford being more passive without undermining selection if it is sufficiently strong to begin with. In short, a strong media might lead to a relatively passive media, even though the media is "working as intended". Third chapter is about electoral campaigns. More precisely, it is a theoretical investigation into one possible audience-related cause for diverging campaign structures of different candidates competing for the same office: state of political knowledge in an electorate. Electorate is assumed to consist of a continuum of voters heterogenous along two dimensions: policy preferences and political knowledge. The latter is assumed to partition the set of voters into ignorant and informed segments, with the former consisting of voters who are unable to condition their voting decisions on the policy dimension. Political competition takes place within a probabilistic voting setting with two candidates, but instead of costless policy proposals as in a standard probabilistic voting model, it revolves around campaigning. Electoral campaigning is modelled as a limited resource allocation problem between two activities: policy campaigning and valence campaigning. The former permits candidates to relocate from their initial policy positions (reputations or legacies), which are assumed to be at the opposing segments of the policy space (i.e. left and right). The latter allows them to generate universal support via a partisanship effect and can be interpreted as an investment into non-policy campaign content such as impressionistic advertising, recruitment of writers capable of producing emotionally appealing speeches, etc. The chapter has two central results. First, a candidate's resource allocation to valence campaigning increases with the fraction of ignorant voters, ideological (non-policy) heterogeneity of informed voters and proximity of candidate's initial position to the bliss point of the informed pseudo-swing voter. The last one results from decreasing relative marginal returns for politicians from converging to pseudo- swing voter's ideal position. Second, even if candidates are otherwise symmetric, a monotonic association between policy preferences and political knowledge can induce divergence into campaign structures. For instance, if ignorance and policy preferences are positively correlated (e.g. less educated preferring more public good) then the left candidate would conduct a campaign with a heavier valence focus and vice versa. Underlying this result is again the decreasing relative marginal returns argument: a candidate whose initial position is already close to that of the informed pseudo-swing voter would benefit more from a valence oriented campaign. An implication of this is that a party that is known having a relatively more ignorant voter base can end up conducting a much more policy focused campaign compared to a party that is largely associated with politically aware voters.
Keywords: political economy; tax enforcement; media; political selection; voting; electoral campaigning